Circadian Rhythms Methods and Protocols - Rosato, Ezio.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
The aim of Circadian Rhythms is to provide a resource that can be adopted by several types of users: those who are new to circadian biology, those who are already active in the field but are interested in learning new techniques and researchers who are considering moving to a new a model system or undertaking comparative studies and would like to consult protocols applied to different organisms before starting the study of new species. This book features a full range of methods that illustrate procedures that have been recently been introduced in circadian studies and by presenting variations to take into account the peculiarities of different model systems.
Overviews -- Light, Photoreceptors, and Circadian Clocks -- Statistical Analysis of Biological Rhythm Data -- Rhythmic Readouts -- Rhythmic Conidiation in Neurospora crassa -- Monitoring and Analyzing Drosophila Circadian Locomotor Activity -- Automated Video Image Analysis of Larval Zebrafish Locomotor Rhythms -- Locomotor Activity in Rodents -- Analysis of Circadian Leaf Movement Rhythms in Arabidopsis thaliana -- Detection of Rhythmic Bioluminescence From Luciferase Reporters in Cyanobacteria -- Analysis of Rhythmic Gene Expression in Adult Drosophila Using the Firefly Luciferase Reporter Gene -- Monitoring Circadian Rhythms in Arabidopsis thaliana Using Luciferase Reporter Genes -- Identification of Clock Genes -- Specialized Techniques for Site-Directed Mutagenesis in Cyanobacteria -- Novel Strategies for the Identification of Clock Genes Neurospora With Insertional Mutagenesis -- Mutagenesis With Drosophila -- Mutagenesis in Arabidopsis -- Yeast Two-Hybrid Screening -- Microarrays -- Microarrays -- Identification of Clock Genes Using Difference Gel Electrophoresis -- Gene Expression: RNA -- Isolation of Total RNA From Neurospora Mycelium -- RNA Extraction From Drosophila Heads -- Extraction of Plant RNA -- RNA Extraction From Mammalian Tissues -- Northern Analysis of Sense and Antisense frequency RNA in Neurospora crassa -- RNase Protection Assay -- Quantitative Polymerase Chain Reaction -- Gene Expression: Proteins -- Protein Extraction, Fractionation, and Purification From Cyanobacteria -- Protein Extraction From Drosophila Heads -- Plant Protein Extraction -- Protein Extraction From Mammalian Tissues -- Western Blotting -- Coimmunoprecipitation Assay -- In Vitro Phosphorylation and Kinase Assays in Neurospora crassa -- In Vitro Systems -- Basic Protocols for Drosophila S2 Cell Line -- Coimmunoprecipitation on Drosophila Cells in Culture -- Basic Protocols for Zebrafish Cell Lines -- Manipulation of Mammalian Cell Lines for Circadian Studies -- Reporter Assays -- Use of Firefly Luciferase Activity Assays to Monitor Circadian Molecular Rhythms In Vivo and In Vitro -- Suprachiasmatic Nucleus Cultures That Maintain Rhythmic Properties In Vitro -- Microscopy Analysis -- RNA In Situ Hybridizations on Drosophila Whole Mounts -- In Situ Hybridization of Suprachiasmatic Nucleus Slices -- Immunohistochemistry in Drosophila -- Immunocytochemistry on Suprachiasmatic Nucleus Slices -- Immunofluorescence Analysis of Circadian Protein Dynamics in Cultured Mammalian Cells.
Keywords: Biochemistry; Cell biology; Animal genetics; Plant genetics; Biochemistry, general; Cell Biology; Animal Genetics and Genomics; Plant Genetics and Genomics